If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -1(x + 6) = 8x + 6(2 + -1x) Reorder the terms: 4x + -1(6 + x) = 8x + 6(2 + -1x) 4x + (6 * -1 + x * -1) = 8x + 6(2 + -1x) 4x + (-6 + -1x) = 8x + 6(2 + -1x) Reorder the terms: -6 + 4x + -1x = 8x + 6(2 + -1x) Combine like terms: 4x + -1x = 3x -6 + 3x = 8x + 6(2 + -1x) -6 + 3x = 8x + (2 * 6 + -1x * 6) -6 + 3x = 8x + (12 + -6x) Reorder the terms: -6 + 3x = 12 + 8x + -6x Combine like terms: 8x + -6x = 2x -6 + 3x = 12 + 2x Solving -6 + 3x = 12 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -6 + 3x + -2x = 12 + 2x + -2x Combine like terms: 3x + -2x = 1x -6 + 1x = 12 + 2x + -2x Combine like terms: 2x + -2x = 0 -6 + 1x = 12 + 0 -6 + 1x = 12 Add '6' to each side of the equation. -6 + 6 + 1x = 12 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = 12 + 6 1x = 12 + 6 Combine like terms: 12 + 6 = 18 1x = 18 Divide each side by '1'. x = 18 Simplifying x = 18
| 3(5x-2)/5x | | 2x-4+2(x-5)=2(x+3) | | 0.05(x-200)=240 | | 4x^2-2.2x+0.0024=0 | | 7y-4x-5=0 | | -6=-10w+9 | | 2w+4=2+6 | | (X^2+x-6)/(3x+3)*(x+1)/(x^2+2x-3) | | 3(2x-3)+2x=15 | | 5u^2=7u+6 | | 3v^2-3=240 | | (5x^6)(8)= | | 8-1x=-5 | | (5x^6)*(8)= | | (3/5)x+4=(1/5)x+5 | | 10-0.6-3.1= | | (2a^3+a-4)-(3-4a^3-9a^2)= | | 9e^8x/5x+3 | | (3x+2)+(x+6)= | | -175+219= | | 2w^2-180w+2800=0 | | t^5*t^6= | | 5/6-5/9/4/5 | | 4x^2(x-5)= | | 5x^2-2x-6=-3x^2+2x | | ln=5(x+1) | | 1/3(2x-7)=3 | | 20=5.2x-08 | | w=5y+8 | | 20=5.2-0.8 | | 1/4(-4)=y | | 3(p+20)=81 |